Upotreba Survival analize u istraživanju varijabilnosti listanja provenijencija obične jele (Abies alba Mill.) - Ivanković, Mladen, inženjer šumarstva (Array, 2008)
This paper presents results of European fir (Abies alba Mill.) provenance experiment tested for flushing variability and the influence of the number of lateral buds on flushing. The data were gathered on a European fir provenance experiment laid out in 2000 on Brlo{ko locality, Forest office Fu`ine, Forest administration branch Delnice. During the spring of 2001, a phenology monitoring was carried out taking into account three phenophases: winter bud (0), bud expansion (1) and open bud (2). Phenology monitoring was carried out once a week. Data processing was carried out by Survival analysis in Statistica program. The results indicate the existence of significant differences in flushing of European fir provenances. Survival analysis has proven to be useful for the analysis of flushing variability and similar types of research.